Pollution affecting respiratory health of regular urban cyclists (2018)
"Around 15,000 people die every year due to illnesses associated with pollution. Cyclists are especially affected by this because their elevated respiratory frequency forces them to inhale particulate matter (2.5PM). In this study, an anti-polution mask for urban cyclists is proposed, designed, and manufactured in order to prevent respiratory diseases among this population."--Tomado del Formato de Documento de Grado